Influences of Serendipita indica and Dictyophorae echinovolvata on the Growth and Fusarium Wilt Disease Resistance of Banana - Chunzhen Cheng; Fan Liu; Bin Wang; Pengyan Qu; Jiapeng Liu; Yongyan Zhang; Wei Liu; Zheng Tong; Guiming Deng (Biology, 2022)
Recently, many control methods have been tried and applied in the Fusarium wilt disease control of banana and have achieved definite progresses. In this study, by using ‘Zhongjiao No.3’ and ‘Zhongjiao No.4’ banana seedlings as materials, the effects of Serendipita indica and bamboo fungus (Dictyophorae echinovolvata) culture substrates on the growth and Fusarium wilt disease resistance of banana were investigated. Results showed that the plant height, leaf length, leaf width, root length and root thickness, aboveground part fresh weight, root fresh weight, and relative chlorophyll content and nitrogen content in leaves of banana seedlings colonized with S. indica were all greater than those of non-colonized controls, while these parameters of banana seedlings grown in nutrient soil containing D. echinovolvata culture substrates were significantly suppressed. Both S. indica non-colonized and colonized seedlings cultivated in nutrient containing 1/4 D. echinovolvata culture substrates showed much milder symptoms compared with those cultivated in normal nutrient soil, indicating that the addition of bamboo fungus substrates to the soil can enhance the Fusarium wilt resistance of banana. The results obtained in this study can provide a basis for the application of S. indica and bamboo fungus in the prevention and control of banana Fusarium wilt disease.